Validação da Parental Perception on Antibiotics Scale: versão brasileira - Lima, Glaubervania Alves (2023)
The Parental Perception on Antibiotics Scale (PAPA Scale) is an instrument for assessing parents' perception of the factors that influence the use of antibiotics in their children, developed in English, translated and adapted into Brazilian Portuguese. It aims to validate the content of the Parental Perception on Antibiotics Scale, Brazilian version (PAPA-Br); evaluate the reliability of the PAPA-Br for analyzing the parents' perception of the factors that influence the administration of antibiotics to their children; and to verify the association between the parents' sociodemographic characteristics and the PAPA-Br factors. Methodological validation study of the PAPA-Br with evaluation of its psychometric properties. The scale comprises 36 items, divided into six components: Knowledge and Beliefs; Behavior; Information sources; Accession; Awareness of antibiotic resistance; and Parents' perception of physicians' prescribing behavior. The study was developed in two stages: I- Content validation: carried out by a committee composed of 24 judges; and II – Reliability assessment: homogeneity and stability, with a sample of 209 parents of children who used antibiotics in the last six months. Data collection took place from September to November 2022, through a telephone interview or self-completion of a sociodemographic and clinical characterization instrument and the PAPA-Br scale. Data were analyzed using the Statistical Package for Social Sciences (SPSS), version 20, using descriptive and analytical statistics. For content analysis, the content validity coefficient was calculated; for homogeneity Cronbach's alpha; and for stability the application of the test-retest, using the Wilcoxon test. The association of PAPA-Br with parents' sociodemographic characteristics was analyzed using Student's t test and ANOVA. Project approved by the Research Ethics Committee. As a result, the total content validity coefficients of the language clarity, practical relevance and theoretical relevance criteria were 0.94; 0.97 and 0.97, respectively. Homogeneity showed a Cronbach's alpha of 0.98 for the judges' responses and 0.80 for application with the target audience, confirming the instrument's reliability. All scale factors had a value of p>0.05 and only items 3 and 22 had a significant difference, confirming the stability of the instrument. An association was observed between the parents' sociodemographic characteristics and the scale factors: brown/black parents, with an affective relationship, lower level of education and lower income had higher scores in the factors knowledge and beliefs, behavior and adherence. Health professionals, with a higher level of education and higher income, showed better results related to awareness of antibiotic resistance. It is concluded that the PAPA-Br is a valid, reliable instrument capable of assessing the perception of Brazilian parents regarding the use of antibiotics by their children.